Bearing Characteristics of Moso Bamboo Micropile-Composite Soil Nailing System in Soft Soil Areas - Zhihe Cheng; Yousheng Deng (Advances in Materials Science and Engineering)
Based on the characteristics of moso bamboo including high short-term strength, stable performance, and ability to provide temporary support for shallow foundation pits in soft soil, the stress characteristics and supporting effects of the ecological composite supporting system have been explored through model tests and numerical calculation analysis of the moso bamboo micropile-composite soil nailing structure. The results showed that the bamboo pile can effectively control the horizontal deformation of the side wall of the foundation pit and the ground surface settlement, achieving a relatively satisfactory supporting effect. Furthermore, the bamboo pile has visibly bent in middle and lower parts, where the regional shear point is most likely to appear, the axial force of the soil nail is distributed in an oval pattern with a smaller force on both sides and a larger force in the middle part, the maximum axial strain is 447.3 με, and the axial force of the soil nails in each row follows a similar trend. The synergy of piles and soil nails can delay the formation of the slip surface, therefore enhancing the overall bearing capacity of the foundation pit. These results can shed light on the support mechanism and engineering design of bamboo piles in shallow soft soil foundation pits.